2010
DOI: 10.1111/j.1471-0528.2010.02533.x
|View full text |Cite|
|
Sign up to set email alerts
|

Uterine rupture after previous caesarean section

Abstract: Objective To determine the risk factors, percentage and maternal and perinatal complications of uterine rupture after previous caesarean section.Design Population-based registry study.Population Mothers with births ‡28 weeks of gestation after previous caesarean section (n = 18 794), registered in the Medical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
69
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 47 publications
9
69
2
Order By: Relevance
“…Previous studies reported the incidences of uterine rupture in women with prior CS from 0.22% to 1.69%34561419 and these were similar to the results of this study, with an overall rate of 0.5%. The incidence of uterine rupture was highest in low-HDI countries (1.0%), and the multivariate analysis identified giving birth in low-HDI countries as a factor associated with uterine rupture.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies reported the incidences of uterine rupture in women with prior CS from 0.22% to 1.69%34561419 and these were similar to the results of this study, with an overall rate of 0.5%. The incidence of uterine rupture was highest in low-HDI countries (1.0%), and the multivariate analysis identified giving birth in low-HDI countries as a factor associated with uterine rupture.…”
Section: Discussionsupporting
confidence: 91%
“…The reported incidence of uterine rupture among women with prior CS ranged from 0.22% to 0.5% in some developed countries3456. The risk factors for uterine rupture in women with a history of CS include prior classical incision, labour induction or argumentation, macrosomia, increasing maternal age, post-term delivery, short maternal stature, no prior vaginal delivery, and prior periviable CS47891011.…”
mentioning
confidence: 99%
“…Furthermore, our systematic search identified multiple large studies regarding uterine ruptures in which information on the tocogram was not provided, which could entail publication bias. For example, Al-Zirqi et al ( n  = 94) and Kwee et al ( n  = 98) identified a total of 192 uterine ruptures, yet both studies did not analyze uterine activity patterns [8, 33]. And we excluded the study of Kayani et al, because there was no uterine activity evaluation, while they do report that ‘the intrauterine pressure catheters recording have contributed to the diagnosis of uterine rupture’ [34].…”
Section: Discussionmentioning
confidence: 99%
“…National guidelines for diagnosis, monitoring and treatment of maternal and fetal complications have been updated regularly since 1995, but lack of adherence has been reported 19–22. Caesarean section also increases the risk of maternal complications both in the actual and subsequent pregnancies 23,24. Within-country variation of caesarean section rates may have an impact on maternal morbidity.…”
Section: Discussionmentioning
confidence: 99%